1 - L'administration sénégalaise et la gestion des "fléaux sociaux"*: by Momar Coumba Diop - Momar Coumba Diop, (Africa Development, 1990)
The data published in this paper are mostly the results of a documentary search. The study begins with a presentation of the concept of "social plague" which shows that it varies considerably with the concerns of public powers. Then a short presentation of the evolution of the concept since independence is given. Then, on the basis of colonial heritage an attempt has been made to explain how the Senegalese administration has managed some "plagues" like alcoholism, the use of drugs, prostitution and begging. Available infoimation show that it is the setting up of a body of laws of growing harshness which has been the response. Certain social groups related to crime, idleness and disorder have been victim of an often brutal policy of control of plagues as is shown by the study on begging. The cases studied have shown how the state has been induced to creating an ideology of rejection of "parasitism" in the urban area.